Relative time rates in dynamic timed automata. (2016) - Layadi, Saïd; Kitouni, Ilham; Belala, Nabil; Saïdouni, Djamel-Eddine
The verification of dynamic real-time systems, such as ad-hoc networks and ambient systems needs formal approaches and frameworks enabling tool construction. In this paper, the decidability question is addressed on a class of timed automata, the dynamic timed automata with relative time rates model (rd-TA). We introduce rd-TA as a simple extension of standard timed automata in which any process may spawn new processes. In this model, the distributed timed systems are formed by a set of dynamic timed automata. Each automaton is characterised by a set of local clocks that evolve at different but relative rate of the clocks of the other components. The main contribution is the consideration of slope parameter (which is the ratio of clock rates). This parameter helps us to explore the semantics based on region abstraction for decidability assessment and proof.